Models to Enhance Students Analytical Thinking Skills: A Literature Review - Siti Zalika ROSLY; Nazreen SAHOL HAMID; Melissa MAM YUDI (Communications of International Proceedings, 2021)
Analytical thinking skill refers to the ability to scrutinize and break down facts, issues, events or any other matters into elements such as strengths and weaknesses, functions and purposes as well as reasons and principles (Amer, A., 2005; Montaku, S., 2011). It is also the capability to understand the relationship between those elements (Farex, 2010), which links will be applied to identify the real cause of what happened (Chareonwongsak, C., 1999), that subsequently used to develop solutions to resolve the issues identified. As it enables students to find solutions to specific problems, make concrete decision, and plan action to solve those problems (Raiyan et al 2015), this skill contributes significantly to the current and future development of students’ high level thinking skills. A review on the academic literature reveals that these are the models used in enhancing students analytical thinking skill; (1) Model of Guided Inquiry, (2) Model of Problem Based Learning, and (3) Model of Group Investigation, (Sartika, 2018). This paper attempts to explore the benefits and limitations of each model in enhancing students analytical thinking skills.  We offer insights which are significant for students pursuing professional accounting education.
Keywords: Analytical thinking skills; accounting; education